Isolation and identification of polyphenols from Marsilea quadrifolia with antioxidant properties in vitro and in vivo. Issue 12 (17th June 2016) - Zhang, Yuan; Tian, Hai-Yan; Tan, Ya-Fang; Wong, Yuk-Lau; Wu, Hoi Yan; Jia, Jun-Feng; Wang, Guo-En; Gao, Jing-Jing; Li, Yi-Fang; Kurihara, Hiroshi; Shaw, Pang-Chui; Jiang, Ren-Wang
Abstract: Marsilea quadrifolia is an edible aquatic medicinal plant used as a traditional health food in Asia. Four new polyphenols including kaempferol 3- O -(2″- O - E -caffeoyl)- β -d -glucopyranoside (1 ), kaempferol 3- O -(3″- O - E -caffeoyl)- α -l -arabinopyranoside (3 ), 4-methy-3′-hydroxypsilotinin (4 ) and (±)-( E )-4b-methoxy-3b, 5b-dihydroxyscirpusin A (18 ) together with 14 known ones (2, 5 –17 ) were isolated from the ethanol extract of M. quadrifolia . Structures of the new compounds were elucidated by extensive spectroscopic analyses. In DPPH and oxygen radical absorbance capacity antioxidant assays, some compounds showed stronger antioxidant activities and quercetin (9 ) was the most potent antioxidant in both assays. In a restraint-induced oxidative stress model in mice, quercetin significantly attenuated the increase in plasma ALT and AST levels as well as liver MDA content of restrained mice. Liver SOD activity was also significantly increased by quercetin, indicating a significant in vivo antioxidant activity. As a rich source of polyphenols with strong antioxidant activities, M. quadrifolia may be developed to a product for relieving oxidative stress. Abstract :